2005
DOI: 10.1093/ajcn/82.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-sensitizing effects of dietary resistant starch and effects on skeletal muscle and adipose tissue metabolism

Abstract: These results suggest that dietary supplementation with resistant starch has the potential to improve insulin sensitivity. Further studies in insulin-resistant persons are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
234
2
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(254 citation statements)
references
References 42 publications
7
234
2
5
Order By: Relevance
“…Dietary fibers are classified into two major categories, starches and non-starch polysaccharides. Food and Agricultural Organization considered resistant starch (starch that escapes from digestion in healthy individuals) from potato a beneficial carbohydrate in intestinal and colonic health as well as its metabolic benefits in glycemic management [20,21]. Non-starch polysaccharide includes the components of the plant cell wall such as cellulose [22].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibers are classified into two major categories, starches and non-starch polysaccharides. Food and Agricultural Organization considered resistant starch (starch that escapes from digestion in healthy individuals) from potato a beneficial carbohydrate in intestinal and colonic health as well as its metabolic benefits in glycemic management [20,21]. Non-starch polysaccharide includes the components of the plant cell wall such as cellulose [22].…”
Section: Introductionmentioning
confidence: 99%
“…Breath hydrogen, an indicator of colonic fermentation, also correlated positively with satiety (r = 0.27; p < 0.01) and inversely with GE rate (r = −0.23; p < 0.05) (Nilsson et al, 2008). Other studies demonstrated that RS also plays a role in reduction of postprandial blood glucose and insulin responses, which may be linked to increased satiety (Anderson et al, 2002;Behall et al, 2006;Bornet et al, 2007;Noakes et al, 1996;Quílez et al, 2007;Robertson et al, 2003Robertson et al, , 2005van Amelsvoort and Weststrate, 1992).…”
Section: Resistant Starches (Rs)mentioning
confidence: 89%
“…It was also shown that the intake of 30 g of RS per day, for 4 weeks (healthy humans), improves insulin sensitivity, and SCFA concentrations (acetate and propionate) were higher than in the control group [10]. In addition to a possible increase in insulin sensitivity, Menezes et al [12], in a previous trial with healthy volunteers, observed that the increase in the area under the curve for glucose after ingestion of UBM and UBS was 90 and 40 % lower than the reference food, respectively, which should promote a decreased insulin release.…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 95%
“…A study developed by Robertson et al [10] observed that the consumption of RS for 4 weeks caused a decrease in insulin levels and it suggests that these effects may be related to changes in the SCFA peripheral metabolism. In an in vitro model, the SCFA activated the FFAR2 (free fat acid receptor 2), which promote the release of GLP1 (glucagon like-peptide 1), a hormone involved in insulin metabolism [11].…”
Section: Introductionmentioning
confidence: 99%